The Effect of Intravitreal Anti-VEGF on the Pigment Epithelial Detachment in Eyes with the Exudative Type of Age-Related Macular Degeneration. (January 2015) - Kalouda, Pelagia; Anastasakis, Anastasios; Tsika, Chrysanthi; Tsilimbaris, K. Miltiadis
Abstract Purpose: To evaluate the effect of anti-VEGF treatment on pigment epithelial detachment (PED) secondary to the exudative type of age-related macular degeneration (AMD). Methods: Retrospective analysis of 30 eyes (28 patients) with exudative AMD accompanied by PED (receiving anti-VEGF injections). Alterations of the PED morphology were qualitatively assessed with optical coherence tomography (OCT). Changes in best-corrected visual acuity (BCVA) and number of injections were compared to 30 control eyes (30 patients) exhibiting exudative AMD without PED. Results: Mean follow-up was 19.8 months. Changes of the extent of PED were as follows: unchanged: 11 eyes (36.7%); reduced: 12 (40%); significantly reduced: 7 (23.3%). Mean paired difference in BCVA was −0.08 logMAR (p = 0.46) and in the number of injections was 2.1 injections (p = 0.04). Conclusions: A substantial number of the studied patients showed reduction of the extent of the PED after anti-VEGF treatment. The PED group required a higher number of injections.